INDONESIA DEFENSE DIPLOMACY IN ACHIEVING NATIONAL INTEREST - Sudarsono, Budyanto Putro; Mahroza, Jonni; D.W., Surryanto (Indonesia Defense University, 2018)
In achieving and securing national interests, diplomacy always plays significant role. In its implementation, the state uses all of its nationally available resources including military, economy, politics, intelligence and any other resources available. The use of military as an instrument in diplomacy is inevitable. The general consensus is that negotiation forms a core component of diplomacy. Winning in negotiation, therefore, can be likened to winning in diplomacy. In order to gain leverage during negotiations, gaining a better bargaining position is an important requirement and this strongly relies on a nation’s power of which one of the key components is the military. In this regard, the military power cannot be separated from state diplomacy. This research is designed to understand the role of Indonesia's defense diplomacy in achieving national interests. The objectives of this research are: First, to analyze the role of Indonesian defense diplomacy in achieving national interests and how to optimize it, and secondly, to analyze the factors that influence this role. This research employs qualitative method. All data is obtained through observation, interviews and literature studies. Data analysis is carried out simultaneously with data collection when the researcher is in the field. The research location is at Jakarta City. We can draw two conclusions from the result of the research: 1) The role of defense diplomacy in achieving national interests has not been optimal and its achievements are still limited to defense issues only; 2) Factors influencing the role of defense diplomacy include the capacity and capability of Indonesian Armed Forces (TNI), cooperation between agencies, and formulation of diplomacy strategy.Keywords: Defense diplomacy, diplomacy strategy